1985
DOI: 10.1007/bf00928339
|View full text |Cite
|
Sign up to set email alerts
|

Trichuris muris: Structure and formation of the egg polar plugs

Abstract: The structure and development of the polar plugs of Trichuris muris eggs were observed by light and electron microscopy. Initial stages in plug formation commenced in the spermatheca of the adult female where two polar papillae became delimited from the remainder of the oocyte cytoplasm. These papillae exhibited a discrete PAS positive reaction and were regarded as prospective plug regions from which cytoplasmic granules were absent. Glycogen rosettes, initially concentrated in these prospective areas, were la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…To test the functional role of FIBCD1 expression on IECs in vivo, we employed the parasitic whipworm Trichuris muris, a widely used model of intestinal helminth infection that is transmitted through ingestion of chitin-containing embryonated T. muris eggs (Preston and Jenkins, 1985;Cliffe and Grencis, 2004;Klementowicz et al, 2012). We identified that FIBCD1 recognized and specifically bound the chitin-rich polar plugs of T. muris eggs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test the functional role of FIBCD1 expression on IECs in vivo, we employed the parasitic whipworm Trichuris muris, a widely used model of intestinal helminth infection that is transmitted through ingestion of chitin-containing embryonated T. muris eggs (Preston and Jenkins, 1985;Cliffe and Grencis, 2004;Klementowicz et al, 2012). We identified that FIBCD1 recognized and specifically bound the chitin-rich polar plugs of T. muris eggs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that the factor affecting egg hatching was unlikely to be a microbially derived part of the supernatant. The study also established the necessity of having an intact bacterial structure in the case of E. coli as clustering of green-fluorescent tagged E. coli around the poles of the helminth eggs where worms emerge was observed (Preston and Jenkins, 1985), demonstrating that a component of the bacterial cell surface played a role.…”
Section: T H E E F F E C T O F H E L M I N T H I N F E C T I O N O N mentioning
confidence: 94%
“…The innermost layer consists of impermeable lipid, the second of chitin/protein complex fibrils that provides structural support, while the outermost layer is a vitelline layer composed of lipoproteins (Wharton 1980;Wharton and Jenkins 1978). The structure of the polar plugs of Trichuris resembles the rest of the eggshell, but the chitinuous layer appears to have lower protein concentration (Preston and Jenkins 1985;Wharton and Jenkins 1978). The polar plugs of TSO are degraded and mechanically punctured by the larva during the hatching process, after which the larva emerges (Beer 1973a, b).…”
Section: Introductionmentioning
confidence: 97%